Probiotics to prevent necrotizing enterocolitis in very low birth weight infants: A network meta-analysis - Zhou, Ke-Zhao; Wu, Kang; Deng, Lin-Xuan; Hu, Man; Luo, Yu-Xiang; Zhang, Li-Yan (Frontiers in Pediatrics, 2023)
Abstract: Objective: This study aims to review the evidence for the optimal regimen of probiotics for the prevention of necrotizing enterocolitis (NEC) in very low birth weight infants. Design: Through searching PubMed, EMBASE, Cochrane Library, and Web of Science till September 2022, only randomized controlled trials were included to evaluate the optimal regimen of probiotics for the prevention of NEC in very low birth weight infants. The methodological quality of the included studies was assessed by the Cochrane risk of bias assessment tool (RoB 2), and the collected data were analyzed accordingly using Stata software. Results: Twenty-seven RCTs were included, and the total sample size used in the study was 529. The results of the network meta-analysis showed that Bovine lactoferrin + Lactobacillus rhamnosus GG (RR 0.03; 95% CI 0.00-0.35), Lactobacillus rhamnosus + Lactobacillus plantarum + Lactobacillus casei + Bifidobacterium lactis (RR 0.06; 95% CI 0.00-0.70), Bifidobacterium lactis + inulin (RR 0.16; 95% CI 0.03-0.91) were superior to the control group (Bifidobacterium lactis + Bifidobacterium longum) in reducing the incidence of NEC. The reduction in the incidence of NEC were as follows: Bovine lactoferrin + Lactobacillus rhamnosus GG (SUCRA 95.7%) ＞ Lactobacillus rhamnosus + Lactobacillus plantarum + Lactobacillus casei + Bifidobacterium lactis (SUCRA 89.4%) ＞ and Bifidobacterium lactis + inulin. Conclusions: This network meta-analysis suggests that Lactobacillus rhamnosus GG combined with bovine lactoferrin maybe the most recommended regimen for the prevention of NEC in very low birth weight infants.